1977
DOI: 10.1104/pp.60.4.504
|View full text |Cite
|
Sign up to set email alerts
|

Polarographic Study of Ammonia Assimilation by Isolated Chloroplasts

Abstract: Illuminated pea (Pisum sativum) chloroplasts catalyze (ammonia plus a-ketoglutarate [a-KGJ)-dependent 02 evolution at rates which are commensurate with other estimates of the flux of assimilated nitrogen (mean of eight determinations, 8.3 ,umole per mg chlorophyl per hour, SD 2.4). The reaction was usually initiated with 1 mm ammonia after preincubating chloroplasts in the presence of a-KG, ADP, pyrophosphate, and MgCl2.Progressive increases in ammonia concentration gave Vmax/2 at 0.2 mm (approximately) and Vm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…The glutamine and 2-0G-supported O 2 evolution described here for cyanelles was also described for chloroplasts and attributed to ferredoxin-dependent GOGAT (Anderson and Done, 1977;Woo and Osmond, 1982;Dry and Wiskich, 1983). 2-0G is transported into chloroplasts by a specific permease which shows some overlapping specificities with the dicarboxylate carrier but is clearly distinct from it.…”
Section: Discussionsupporting
confidence: 66%
“…The glutamine and 2-0G-supported O 2 evolution described here for cyanelles was also described for chloroplasts and attributed to ferredoxin-dependent GOGAT (Anderson and Done, 1977;Woo and Osmond, 1982;Dry and Wiskich, 1983). 2-0G is transported into chloroplasts by a specific permease which shows some overlapping specificities with the dicarboxylate carrier but is clearly distinct from it.…”
Section: Discussionsupporting
confidence: 66%
“…In vitro Fd‐GOGAT assay showed that Fds reduced with NADPH via FNRs display a several‐fold higher ability to donate electrons to GOGAT (Table 2) than does photoreduced Fd [34]. In spite of the low FNR and Fd concentrations in BSCs (30 and 40 μ m ) [35,36], a close location of FNRs, Fds and Fd‐GOGAT on the thylakoid membrane [25,37] allows protein–protein complex formation essential for the GOGAT reaction [24].…”
Section: Discussionmentioning
confidence: 99%
“…During the course of photorespiratory NH3 reassimilation by intact chloroplasts, glutamate synthase and glutamine synthetase present in the stromal space established a selfsustaining system for ammonia incorporation where glutamine synthetase initiates the net synthesis of glutamate at the expense of 2-oxoglutarate [257]. Under these conditions, glutamate was continuously excreted from the chloroplasts in exchange for 2-oxoglutarate [258]. The marked effect of malate on the rate of glutamate excretion, observed by Woo and Osmond [259], led to the demonstration that 2-oxoglutarate is transported inward on a 2-oxoglutarate translocator and glutamate outward on a dicarboxylate translocator with malate as the counterion for both translocators in a cascade-like manner [260 -2621.…”
Section: Dicarboxylate Translocatorsmentioning
confidence: 99%
“…Under these conditions, glutamate was continuously excreted from the chloroplasts in exchange for 2-oxoglutarate [258]. The marked effect of malate on the rate of glutamate excretion, observed by Woo and Osmond [259], led to the demonstration that 2-oxoglutarate is transported inward on a 2-oxoglutarate translocator and glutamate outward on a dicarboxylate translocator with malate as the counterion for both translocators in a cascade-like manner [260 -2621.…”
Section: Dicarboxylate Translocatorsmentioning
confidence: 99%